Peranan Informasi Akuntansi Manajemen Dalam Mewujudkan Efisiensi Usaha Peternakan Ayam (Studi Kasus pada Peternak Kemitraan Ayam Daging Jenis Jantan di Kecamatan Kanigoro, Kabupaten Blitar) - Yekti, Muhammad Yoga Pratita; Diana, Nur; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2025)
This study analyzes the role of management accounting information in improving business efficiency in broiler chicken farming under a partnership scheme in Kanigoro District, Blitar Regency. A qualitative approach was applied through in-depth interviews, observation, and documentation involving three partner farmers selected using snowball sampling. The findings show that management accounting information supports business planning, cost control, decision-making, and operational efficiency. Farmers utilize historical data on feed, veterinary expenses, labor costs, and production results to prepare budgets and optimize operational strategies. Systematic financial recording enables them to control expenses, minimize waste, and make data-driven decisions, such as adjusting chicken populations and selecting feed types. Moreover, management accounting information enhances business efficiency by enabling better resource allocation, structured evaluation, and improved decision-making accuracy. However, challenges remain, including limited accounting literacy, reliance on manual records, and the lack of integrated financial systems. The study suggests improving accounting literacy and developing a modern Management Accounting Information System (MAIS) to enhance data accuracy, managerial capability, and sustainable practices in poultry farming.Keywords: Management accounting information, cost control, business planning, decision-making, business efficiency, partnership farming